Manajemen Strategik Pada Pendidikan Indonesia Jenjang Perguruan Tinggi Selama Pembatasan Sosial Pandemi Covid-19 - Tatiek Ekawati Permana; Agus Rahayu; Lili Adi Wibowo (IKOPIN, 2020)
Covid-19 disease has alarming public since early 2020 that on March 11, 2020 WHO has stated the coronavirus plague as global pandemic. The practice of social distancing policy is a tough choice for every country to prevent the covid-19 due to the negative impact of this policy on various aspects of life. College education is one of the areas affected by social distancing policies during the coronavirus pandemic. The government's decision to move the process of teaching and learning in campus to become at home suddenly creates difficulties for many parties. Moving on from these conditions, the authors conducted a study with the aim of analyzing and describing the implementation and evaluation of strategic management in an effort to maintain the continuity, effectiveness and quality of college education in Indonesia during the practice of social distancing. The research conducted is a qualitative research with descriptive method. Various adjustments need to be made by lecturers, students, and university stakeholder in overcoming problems during lecturing activities at home. And how this condition becomes an opportunity in the development of Indonesian education.